Study on the effect of activated coal gangue on the mechanical and hydration properties of cement - Zhu, Zewen; Liu, Chaoqun; Mao, Lin; Han, Zhixing; Chen, Leiwei; Zou, Huijie; Li, Lianghua; Yu, Pengfei; Dong, Jingliang; Zhang, Yonggang (Frontiers in Materials, 2023)
This study aims to minimize cement's carbon emissions and investigate the viability of employing activated coal gangue as an additional cementitious ingredient. By analyzing the effects of water-cement ratio, ages, and amount of activated gangue dosing on the compressive and flexural strength of cementitious sand specimens, this paper investigated the effects of activated gangue on mechanical properties, hydration products, hydration process, and hydration degree. The impacts of activated gangue on the hydration products and microstructure of cement were examined using XRD, SEM, and TG/DTG systems. High levels of active SiO2 and Al2O3 in the activated gangue can react with Ca(OH)2 and have a high secondary hydration reaction activity. The hydrated calcium silicate and hydrated calcium aluminate gels produced by the subsequent hydration process can reduce the porosity of hardened cement and boost cement matrix strength. The 28d flexural and compressive strengths rise by 11.69% and 11.82%, respectively, in comparison to specimens mixed with 30 wt. quartz powder. When activated gangue is mixed with cement, the early hydration rate of the cement may be successfully decreased while the later hydration rate is increased.